Success Model Partnership Program SME At PT. Perkebunan Nusantara III - Junaidi, Junaidi; Lubis, Zulkarnain; Effendi, Ihsan (Journal Research of Social Science, Economics, and Management, 2023)
Small medium enterprises is one of the business units that help the country a lot in reducing the unemployment rate. This sector makes a major contribution in supporting the national economy. Real steps and efforts are needed to support and increase the power of SMEs. The main objective of this study is to determine the direct and indirect effects of HR experience, capital, knowledge, social networks, social media, perceived customer benefits, and perceived competitive value on the performance of SMEs through partnership programs. The approach in this research is causal research (cause and effect). The population in this study is the SME business actor who are fostered at PT. Perkebunan Nusantara III, with total of 243 SME business actors. While the sampling technique used a saturated sample where 243 SMEs were sampled in this study. Data collection techniques used a questionnaire with an ordinal measurement scale. Data analysis used AMOS based Structural Equation Modeling (SEM). The results showed that the direct experience of human resources, capital, social networks, social media, and perceived customer benefits had a significant effect on the partnership program, while knowledge was not significant for the partnership program. The results showed that the direct experience of human resources, capital, social networks, social media, perceived customer benefits, and perceived competitive value had a significant effect on the performance of SMEs, while knowledge was not significant on the performance of SMEs. Indirectly the experience of human resources, capital, knowledge, social networks, social media, perceived customer benefits and perceived competitive value had a significant effect on the performance of SMEs through partnership programs.